2019
DOI: 10.36740/wlek201905126
|View full text |Cite
|
Sign up to set email alerts
|

Ten Indicators Which Characterize Medical-Demographic Processes in Adjacent Regions of Ukraine and Poland

Abstract: Introduction: Medical-demographic processes are one of the main signs of life quality, the level of socio-economic development of society. The aim of the work is to compare and evaluate the medical-demographic processes in the two neighboring regions of neighboring countries, due to their geographical proximity, the ratio of the size of the territories and the population. Materials and methods: The study was conducted on the basis of official statistics published by the State Statistics Service of Ukraine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
(1 reference statement)
0
5
0
2
Order By: Relevance
“…Their results show the positive association between defensive pessimism, purchase intention and long-term investment, and mindset priming's positive mediation. The article (Sułkowski, 2020;Grshybowskyj, 2019) attempts to diagnose the impact of the Covid-19 pandemic on global trends, including organizational processes in enterprises and challenges for organization leaders in many areas. The papers (Bryl, 2020;Rudenko, 2020) indicates the influence of the long-term development of the chosen human capital indices and public health policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results show the positive association between defensive pessimism, purchase intention and long-term investment, and mindset priming's positive mediation. The article (Sułkowski, 2020;Grshybowskyj, 2019) attempts to diagnose the impact of the Covid-19 pandemic on global trends, including organizational processes in enterprises and challenges for organization leaders in many areas. The papers (Bryl, 2020;Rudenko, 2020) indicates the influence of the long-term development of the chosen human capital indices and public health policies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to WHO data, i.e.,Global Health Observatory Data Repository and Framework for alcohol policy in the WHO European Region, this kind of analysis is presented in many works, including M. Marmot et al, F. Baum, J. P. Mackenbach, C. Bambra et al, and further Polish researchers [14][15][16][17][18][19][20]. Comparison of data from some geographically close regions of different countries was carried out in the study of J.Grshybowskyj and co-authors, who found a significant difference in the development processes in terms of medical and demographic indicators [21].…”
Section: Discussionmentioning
confidence: 99%
“…народжених живими у 2000 р. і 14,9 у 2019 р.) та перинаталь ної смертності (10,4 і 8,78 на 1000 народжених живими і мертвими відповідно), принциповою особливістю яких є залежність від медико організаційних чинників і обумовленість соціальними умовами життя населення [3,14,15]. Утримується негативна тенденція до збільшення узагальненого об'єктивного кри терію здоров'я покоління, що народжується, та соціально економічного благополуччя насе лення -частоти недоношених (4,64%у 2000 р., 5,24% -у 2019 р.)…”
Section: вступunclassified